Work, Wages and Welfare in Aboriginal-Non-Aboriginal Relations, British Columbia, 1849-1970 - Lutz, John S. (University of Ottawa, 1995)
This dissertation focuses on the work-for-pay exchange between aboriginal people and immigrants of European stock--the two most prominent cultural groups in the early history of British Columbia--and follows the patterns of this exchange from its origins through to the 1970s. It examines both the material and the rhetorical construction of the "Indian" as a part of British Columbia's labour force, a process described as racialization, and emphasizes, as well, the transformation of meaning inherent in cross-cultural exchange. It is a province-wide analysis, the core of which is a micro-history of one aboriginal group, the Songhees people, who live in the area now occupied by Victoria, the capital city. This examination challenges the long-standing view that aboriginal people were bystanders in the economic development and industrialization of British Columbia outside, and after, the fur trade. From the establishment of the Colony of Vancouver Island in 1849, through Confederation with Canada in 1871 and to the 1885 completion of the Canadian Pacific Railway, aboriginal people comprised the majority of the population in present-day British Columbia, and the majority of the work force in agriculture, fishing, trapping and the burgeoning primary industries. This dissertation charts the subsequent decline in participation of aboriginal people in the capitalist economy from 1885 to 1970. Using a micro-historical study and close attention to aboriginal voices it offers a set of explanations for the changing proportions of work, both paid and unpaid, and state welfare payments. The micro-history reveals that the Songhees people engaged in two distinct but connected economies and were already familiar with forms of labour subordination prior to the European introduction of a capitalist economy. The Songhees participation in paid labour for Europeans was facilitated by these existing forms of labour organization and depended on the co-existence of their other economies; the Songhees used earnings from capitalist paid labour to expand their non-capitalist economies. After 1885, new state policies repressed the non-capitalist aboriginal economics and therefore diminished the underlying motivation for aboriginal participation in capitalist work. At the same time, an influx of labour-market competition and a variety of racialized laws and practices restricted the Songhees' ability to get work. Increasingly they were left with seasonal, low-skill and low-wage labour, a niche that maintained them so long as it was combined with a subsistence economy and involved the full participation of adult and adolescent family members. In the late 1940s and 1950s this pattern too was remade. Legal restrictions dramatically limited the subsistence economies; technological change curtailed the demand for seasonal labour in the canning, fishing and agricultural sectors, particularly affecting aboriginal women workers; and, compulsory schooling regulations began to reduce labour available to the family economy. At the same historic moment when the combined wage and subsistence economies ceased to be able to support them, the state extended some existing social welfare programs, such as Old Age Pension, to Indians, and expanded other programs, including Family Allowance, to all Canadians. In examining the patterns of aboriginal-non-aboriginal exchange relations over the long-term, this dissertation argues that high rates of unemployment and welfare-dependency among contemporary aboriginal communities are relatively recent historical phenomena, with observable roots and causes.